The impact of employee empowerment on continuous improvement of health care: an empirical and comparative study between hospitals - Al-Rjoub, Salameh Radwan; Aldiabat, Bassam Fathi; Ait Yassine, Fatima Lahcen Yachou (Business: Theory and Practice, 2023)
The study has been aimed to know the impact of Employee Empowerment on CI of health care between hospitals (government and private). The required data for the purpose of this study were collected by a questionnaire designed on the basis of related practices. It consisted of 73 items divided into two domains, the first one to measure employee empowerment practices (37 items), and the second one to measure CI practices (36 items). The study sample was applied to the (326) respondents; The total number of respondents from hospitals was 326; That is, 76% of the total number of the target group, which is (431) respondents, with a response rate of 96%, which is high percent because the researcher distributed the questionnaires personally. Using IBM SPSS and a comparative descriptive-analytical approach. Three themes emerged from the respondents’ trends. First, the existence of employee empowerment application in government hospitals was moderately level, and in private hospitals was in a high level, and also the existence of CI application in government hospitals was in a low level, and in private hospitals was in a high level. Second, there is a strong correlation between employee empowerment and CI of health care in hospitals (government, private). Third, there is statistically significant impact at the level (α ≤ 0.05) of the Employee empowerment on CI of health care whether the dimensions of CI are combined or fragmented in hospitals. The limitation of this study was in fixed bureaucracy structure in governmental hospitals and competitiveness issues in private hospitals. The study dealt with a dependent variable that was rarely studied by previous Arab studies and also rarely comparative study between profit and nonprofit hospitals.